A compact multiband band slot antenna for wireless applications. Issue 6 (16th April 2019) - Khan, Imran; Ali, Tanweer; Devanagavi, Geeta D.; Sudhindra, Kumbhashi R.; Biradar, Rajashekhar C.
Abstract : A compact (20 × 20 × 1.6 mm 3 ) planar four band antenna operating at 1.35 (lower Global Navigation Satellite System [GNSS]), 2.57 (lower Worldwide Microwave Access [WiMAX]), 4.57 (C‐band) and for 5.13 GHz (Wireless Local Area Network [WLAN]) is presented. By utilizing slot method in the radiating patch and the ground plane the aforementioned operating bands are achieved. The antenna has a miniaturized dimension of 0.09λ0 × 0.09λ0 × 0.007λ0 (where λ0 is the free space wavelength at the lower frequency of 1.35 GHz, and exhibits good impedance match, acceptable radiation efficiency and stable radiation pattern at the targeted frequencies.